SYRIAN ATTITUDE TOWARD THE PRESERVATION AND MAINTENANCE OF SYRIAN DIALECT AND CULTURE IN JERASH, JORDAN - Engku Suhaimi Engku Atek; Zulazhan Ab. Halim; Hisham Hussain Al Samadi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The study of dialectical variation and cultural maintenance may help in protecting and promoting norms and values in a given community. The inconsistent background of Syrian from Jordanian culture enables a contingency approach for the influence of dialectical variances in cultural activities. The paper aims at examining the role of dialectical variation towards strengthening the relationship between Syrian-Jordanian communities in Jerash city. The paper examines the elements that determine dialect choice in the vicinity. The study investigates dialect and cultural maintenance among Syrian-Jordanian to allow comparison of the potential influences of several parameters on their use on different dialects. The study used the data collected from various participants through interviews and questionnaires to arrive at the findings of the study. Both local and foreign dialects receive significant recognition and functions such as social domains, social activities, social gatherings, religious practices, cultural heritage, to mention a few, in the city. The findings show that dialect maintenance is strictly secure by Syrians in all aspects, except in exceptional cases like feasts, condolences, weddings, buying and selling where they opt for local dialect other than Syrian dialect. It has been observed that socio-demographic factors impact the flow of Syrian dialect and cultural maintenance in Jerash city. The findings discovered that gender contributed to dialect choice and shifting. What appears to be achieved and documented through the current study is that Syrian males are mostly lean to the usage of Jordanian dialect than the Syrian females because the latter hardly utilize Jordanian dialect even while the necessity arose to a large extent. The regular shift of dialect from Syrian to Jordanian or vice versa which equally constitutes the factors responsible for dialect shift is heavily supported by friendship, marriage, religion, relatives, migrations, and good rapport between Syrians and Jordanians.